Implementasi Pendampingan Digital pada UMKM Tempe Kripik Bu Fatim di Kabupaten Trenggalek - Ramadhani, Aulia; Utami, Rizki Amalia; Hermawan, Agus; Winarno, Agung (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The assistance program for the "Bu Fatim" Tempe Chips micro-enterprise was implemented to help the owner tackle several key issues that were hindering the business's growth. The activities aimed to directly involve the partner and focused on actual needs identified in the field. The process began with team preparation, followed by a thorough observation of production activities, marketing practices, and the existing financial record-keeping system. Initial findings revealed that marketing efforts were primarily limited to direct, in-person sales. Additionally, the product packaging did not adequately protect the items during delivery, and financial records were not organized systematically. Based on these observations, the team developed an assistance plan that included creating digital promotional materials, improving packaging design, and introducing a user-friendly bookkeeping application.The implementation of this plan yielded positive outcomes, which included the establishment of a business social media account, the use of better-suited packaging, and more organized financial records. Overall, this program significantly contributed to strengthening the micro-enterprise's readiness to compete in the digital market.